Prenatal diagnosis of true cord knot: a case report - Rafaelano Miranda, Alexander de J. (2025)
The true umbilical cord knot has an incidence at birth of up to 1.22 %. During prenatal ultrasoundscanning, a cloverleaf pattern, the hanging rope sign, fixed loop, cord loop or cyclone sign may be observed. A clinical case of prenatal diagnosis of true cord knot with good perinatal outcome is reported. We present the case of a 28-year-old female patient at 33.1 weeks of gestation. The ultrasound scan showed a cloverleaf pattern, a hanging rope sign and a fixed loop in the umbilical cord, confirming the suspicion of a true cord knot, as shown by color Doppler and 3D imaging. Weeklyfollow-up with Doppler ultrasound and non-stress testing was conducted. A cesarean section was scheduled at 37 weeks, resulting in a newborn weighing 2,870 grams and measuring 47 cm, with no signs of asphyxiation. The diagnosis was confirmed at birth. 3D and 4D ultrasound imaging has proven to be reliable a method for diagnosis, with a sensitivity of 87.5 %, specificity of 99.6 % and precision of 96.9 %. The true knot is associated with adverse neonatal outcomes, including fetal acidosis, meconium in the amniotic fluid, preterm birth, low Apgar at one minute, increased risk of admission to the neonatal care unit, and up to a 4- to 8-fold higher fetal death rate before delivery. The incidental discovery of a true knot presents a dilemma for both the patient and the obstetrician, especially because its surveillance, management, timing and method of pregnancy resolution currently lack an evidence-based approach. With technological advancements and the increasing number of maternal-fetal medicine specialists who use ultrasound techniques to focus on umbilical cord pathology, the prenatal detection rate can be improved, contributing to a reduction in sudden and unexpected perinatal morbidity and mortality